Numerical Study of Powder Flow Nozzle for Laser-Assisted Metal Deposition - Romuald Petkevič (MDPI AG, 2021)
Metal additive manufacturing has received much attention in the past few decades, and it offers a variety of technologies for three-dimensional object production. One of such technologies, allowing large-sized object production, is laser-assisted metal deposition, the limits of which are determined by the capabilities of the positioning system. The already-existing nozzles have either a relatively low build rate or a poor resolution. The goal of this work is to develop a new nozzle with a centered particle beam at high velocity for the laser-assisted metal additive manufacturing technologies. Scientific challenges are addressed with regards to the fluid dynamics, the particle-substrate contact, and tracking of the thermodynamic state during contact. In this paper, two nozzles based on the de Laval geometry with Witoszynski and Bicubic curves of convergence zone were designed; the results showed that the average flow velocity in a Bicubic outlet curve nozzle is around 615 m/s and in Witoszynski this is 435 m/s. Investigation of particle beam formation for the Bicubic curve geometry revealed that small particles have the highest velocity and the lowest total force at the nozzle outlet. Fine particles have a shorter response time, and therefore, a smaller dispersion area. The elasto-plastic particle-surface contact showed that particles of diameter limited up to 3 μm are able to reach experimentally obtained critical velocity without additional heating. For particle sizes above 10 μm, additional heating is needed for deposition. The maximum coefficient of restitution (COR) is achieved with a particle size of 30 μm; smaller particles are characterized by the values of COR, which are lower due to a relatively high velocity. Particles larger than 30 μm are scalable, characterized by a small change in velocity and a rise in temperature as their mass increases.